Eksplorasi Small Area Estimation (SAE) Data SUSENAS Triwulanan dengan Add-Ins Rexcel - Ibnu Santoso (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Statistika STIS, 2018)
Nowadays, the demand of small area data of BPS-Statistics Indonesia is increasing. This condition needs further study about SAE for BPS data. By using SUSENAS quarterly, we want to see how SAE can produce better accuracy for estimation value in small area than design-based. The result show that SAE EBLUP-Fay Herriot can produce better estimation with lower MSE than design-based estimation. This research also create tools to calculate this estimation. The tools was wrapped in Add-Ins Rexcel based on Graphical User Interface ( GUI ). Keywords: EBLUP Fay Herriot, SAE, design-based, SUSENAS, Add-Ins, Rexcel